Seek and you shall find: rediscovery of the Brazilian Euphorbia burchellii (Euphorbiaceae) after nearly a century and a half, with a conspectus of Euphorbia sect. Anisophyllum species in the state of Goiás, Brazil - Silva, Marcos José Da; Feitosa, Gabriel Lucas; Riina, Ricarda (Phytotaxa, 2021)
During a taxonomic study of Euphorbia from Goiás state, Brazil, we came across some small populations of an unfamiliar species of the genus in the Chapada dos Veadeiros region. After detailed analyses of these specimens we concluded that they correspond to E. burchellii (E. section Anisophyllum), a species hitherto known only from its type locality. We present an amended description of E. burchellii, provide the first information about its fruits and seeds, as well as its lectotipification. We also include illustrations and field photographs, comments on its geographical range along with a distribution map, a recommendation for conservation status, phenology, morphological relationships, and systematic position. Finally, we also provide a key to the 14 species of E. section Anisophyllum occurring in Goiás State.